The Rhetoric of Recovery: Can Twelve Step Programs Inform the Teaching of Writing? - Christopher C. Weaver (Journal of the Assembly for Expanded Perspectives on Learning, 2002)
The article examines the spiritual dimensions of recovery programs and explores some of the ways the rhetoric of these programs as well as the structure of twelve step meetings may illuminate the nature of composition classes and particularly of peer writing groups.